Health and safety practice during COVID-19: a case of Siburan clinic / Avon Janius and Musmuliadi Kamaruding - Janius, Avon; Kamaruding, Musmuliadi (2022)
The construction industry remains a critical sector impacted due to the Covid-19 Pandemic outbreak and the continuous rise in Covid-19 cases in the construction sector. The situation demands health and safety practices among the stakeholders to minimize the Covid-19 cases in the construction sector. Thus, the objective of this study is to explore the current practice of health and safety in the construction site during Covid-19 and select the Siburan Clinic project as a case study. This objective was achieved by conducting semi-structured interviews among the parties involved in the Siburan clinic construction project. The finding shows that the health and safety practice in the Siburan Clinic construction project mainly refers to the Standard Operation Procedure (SOP) recommended by the “Jabatan Kerja Raya (JKR)”, “Majlis Keselamatan Negara (MKN)”, and “Construction Industrial Development Berhad (CIDB)”. It can be concluded that the health and safety aspect is an important practice that needs to adapt as it can significantly impact construction progress and its financial management.